Titelblatt zum Jahrestag der Russischen Revolution
1. Jahrestag; Titelblatt; Text:"One Year of REVOLUTION. Celebrating the First Anniversary of the founding of the RUSSIAN SOVIET REPUBLIC. Issued by the Socialist Publication Society, 431 Pulaski Street, Brooklyn, N.Y."; Zeichnung: Arbeiter mitHammer, Besen, Harke; Russische Fahne; Bemerkungen: Reproduktion